Analisa Perbandingan Algoritma Run Length Encoding Dengan Burrows-Wheeler Transform Dalam Kompresi File Video - Muhammad Rizky Ramadhan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Recent technological developments affect file sizes, especially video format files. The video file is large enough to use a lot of storage space, the longer the video duration and the better the video quality, the larger the video file size. Large amounts of data also require a lot of storage space. To do this, we need solutions such as the manufacture of large-capacity storage media. But in the future, the video file size will increase and the video quality will increase, so this solution becomes less effective. Therefore, additional solutions are needed to save storage media space and reduce the size of the data stored. Reducing memory usage and file size without affecting the information in the file can be overcome by compression. Video compression is a data compression process that is carried out on video files to reduce the size of the video file so that it can be stored or sent quickly and efficiently. In the comparison of the two Run Length Encoding algorithms with the Burrows-Wheeler Transform algorithm as follows, the Run Length Encoding algorithm works well on video compression and can achieve very high compression ratios, while the Burrows-Wheeler Transform algorithm concludes that the data size is not reduced. at all, but undergoes a data change or transformation.